a student was given the equation x^2+ 6x -13 = 0 to solve by completing the square, the first step that was written was shown below.

x^2+ 6x= 13

the next step in the student's process was x^2+ 6x + c = 13 + c

part A:

state the values of c that creates the perfect square trinomial.

part B:

explain how the value of c is determined

part A: c=9

part B: c=(b/2)^2=(6/2)^2=9......................................................................................................................................................

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up